ACCURACY AND DIAGNOSTIC UTILITY OF FROZEN SECTION IN THYROID LESIONS: A COMPARATIVE STUDY - Madhuri Mushinam, Sudha; De Padua, Michelle (International Journal of Clinical and Biomedical Research, 2017)
Introduction: Many surgeons perform intra operative frozen section to overcome the limitations of FNAC, to differentiate benign lesions from malignant lesions and to determine the extent of surgery. However, the use and cost effectiveness of FS is controversial in follicular lesions. Nevertheless FS is most useful in cases where FNA results are indeterminate or suspicious and it is a cost effective way to avoid second surgical procedure if a total thyroidectomy is indicated. Aim: To study the diagnostic utility of frozen section and fine needle aspiration cytology thyroid lesions utilizing final histopathology diagnosis as gold standard. Methods: The present study was conducted on 237 cases of thyroid tissue submitted for frozen section for a study period of 5 years. Among those, 95 cases had preoperative FNAC done. Results: The sensitivity, specificity and diagnostic accuracy of FNAC was 42.86%, 96.72% and 82.93%, whereas that of FS was comparatively superior (82%, 100% and 95.65% respectively). Conclusion: Thus, the overall sensitivity, specificity and diagnostic accuracy of FS was superior to that of FNAC in the present series. The main limitations of FS and FNAC in our study were- Capsular/ vascular invasion in follicular neoplasm was not detected in many cases and papillary microcarcinomas were missed. Key words: FNAC; Frozen section; Thyroid lesions.